Teaching Under Pressure - Cockburn, Anne (Taylor & Francis, 1996)
This text is based on the author's research into primary school teacher's stress. The research has been linked with the author's belief in the need to understand ourselves, our personal and professional situations and how they relate. The resulting book is a practical text designed to address the reader in such a way that they can readily identify with what is being discussed. Futhermore, readers are encouraged to explore ways in which they can begin to tackle their own problems.